1999
DOI: 10.1007/s100960050366
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Western Blot Assay to Compare Mother and Newborn Anti- Toxoplasma Antibodies for the Early Neonatal Diagnosis of Congenital Toxoplasmosis

Abstract: The aim of this study was to retrospectively evaluate the performance of a Western blot assay to compare mother and newborn anti-Toxoplasma gondii antibodies for the early neonatal diagnosis of congenital toxoplasmosis. Since specific anti-Toxoplasma IgM or IgA is detected inconstantly at birth in the neonate, the diagnosis of congenital toxoplasmosis is often delayed until 6-9 months, after IgG titers have been observed persistently. In this study, 81 paired samples from 60 mother/child pairs were tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…Western blotting (WB) (268) and an enzyme-linked immunofiltration assay (ELIFA) (258) both allow a qualitative analysis of specific IgG or IgM by a comparison of band patterns or precipitin patterns, respectively, from paired mother-newborn sera with an equal sensitivity (259). Several studies analyzed the diagnostic performance of WB and reported sensitivities of 48 to 50% and 78 to 82% for IgG detection at birth and within the first 3 months of life, respectively (274,320). The combination of WB detection of IgM and IgG allowed a gain in sensitivity, reaching 65 to 79% and 83 to 94% at birth and at 3 months of life, respectively (271,274,320).…”
Section: Diagnosis Of Congenital Toxoplasmosismentioning
confidence: 99%
See 2 more Smart Citations
“…Western blotting (WB) (268) and an enzyme-linked immunofiltration assay (ELIFA) (258) both allow a qualitative analysis of specific IgG or IgM by a comparison of band patterns or precipitin patterns, respectively, from paired mother-newborn sera with an equal sensitivity (259). Several studies analyzed the diagnostic performance of WB and reported sensitivities of 48 to 50% and 78 to 82% for IgG detection at birth and within the first 3 months of life, respectively (274,320). The combination of WB detection of IgM and IgG allowed a gain in sensitivity, reaching 65 to 79% and 83 to 94% at birth and at 3 months of life, respectively (271,274,320).…”
Section: Diagnosis Of Congenital Toxoplasmosismentioning
confidence: 99%
“…Several studies analyzed the diagnostic performance of WB and reported sensitivities of 48 to 50% and 78 to 82% for IgG detection at birth and within the first 3 months of life, respectively (274,320). The combination of WB detection of IgM and IgG allowed a gain in sensitivity, reaching 65 to 79% and 83 to 94% at birth and at 3 months of life, respectively (271,274,320). The combination of ISAGA and WB yielded even better results in those studies.…”
Section: Diagnosis Of Congenital Toxoplasmosismentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of T. gondiispecific IgM antibodies eluted from the filter paper is followed by a request of a blood sample from both the mother and infant for confirmatory testing. Approximately 15 to 20% of these sera have been found to be negative for Toxoplasmaspecific IgM (3,8).Previous studies have shown that transferred maternal and neonate-synthesized T. gondii-specific IgG antibodies can be differentiated by immunoblotting or immunocomplexing (1,4,12,14). Immunoblotting identifies newborns with congenital toxoplasmosis with a sensitivity of ca.…”
mentioning
confidence: 99%
“…Previous studies have shown that transferred maternal and neonate-synthesized T. gondii-specific IgG antibodies can be differentiated by immunoblotting or immunocomplexing (1,4,12,14). Immunoblotting identifies newborns with congenital toxoplasmosis with a sensitivity of ca.…”
mentioning
confidence: 99%